Antibacterial Test of Cherry Leaves Ethanol Extract (Muntingia calabura L.) Against Streptococcus mutans - Amalia, Annora Rizky; Riyan Setiyanto; Alfina Nurrahman; Ariska Rahmawati Utami; Dewi Weni Sari (Crown: Journal of Dentistry and Health Research, 2024)
Introduction: Streptococcus mutans is a bacteria that plays an important role in the occurrence of dental caries. Use of antibiotics to treat infections Streptococcus mutans often causes side effects. Cherry leaves (Muntingia calabura L.) contain active compounds that have the potential to have antibacterial effects. This research aims to determine the inhibitory power of cherry leaf ethanol extract against Streptococcus mutans in vitro. Methods: This research uses an experimental method with a post-test-only control group design. Cherry leaf ethanol extract was made by maceration method using 96% ethanol solvent for 5 days. The antibacterial test was carried out using the paper disc diffusion method with varying concentrations of cherry leaf extract, namely 20%, 40%, and 60% w/v dissolved in 10% DMSO. The positive control used was the amoxicillin antibiotic disc, while the negative control used 10% DMSO. Results: The results of the antibacterial test of the ethanol extract of cherry leaves in this study showed that at a concentration of 20% it had an average inhibitory power of 9.16 mm, the extract with a concentration of 40% had an inhibitory power of 11.33 mm, and at a concentration of 60% it had an inhibitory power of 12. 16mm. The positive control amoxicillin had an inhibitory power of 18.67 mm. Conclusion: Cherry leaf ethanol extract has potential as an alternative therapy to overcome Streptococcus mutans bacterial infections.